Estimating the potato varieties by productivity and biochemical parameters under conditions of Kirov region - Z. F. Sergeeva; N. F. Sintsova; I. V. Lyskova; T. V. Lyskova (Аграрная наука Евро-Северо-Востока, 2018)
Potato is one of the most important foodstulfs for wide layers of population in the Russian Federation. Materials of 2014-2017 competitive testing investigation of potato varieties by productivity and basic biochemical parameters of tubers (the content of dry matter, starch, protein, vitamin C, and reducing sugars) in Kirov region are presented in the article. The objects of study are 9 varieties of two maturity groups: early and middle-early, mid ripening and middle-late. Perspective potato varieties of different terms of maturity combining high productivity and tuber quality have been selected. Within the first group the variety samples bred in Falenki breeding station are chosen: an early sample 179-10, which has an average productivity of 34.8 t/ha, addition to the standard Udacha (All-Russia Research Institute of Potato Farming) is 3.1 t/ha, addition to the standard Nevsky (North West Research Institute of Agriculture)- 8.8 t/ha, tubers are round, of white color, noted for uniformity in nest and good taste; a middle-early sample 90-09 with productivity of 30.6 t/ha and starch content 15.4%. In the second group - a middle sample 109-09 with productivity of 27.9 t/ha, maximum starch content 17%. Within recognized varieties, Chaika (Falenki breeding station) had a higher concentration of starch; a higher content of vitamin С was recorded in Viza (Falenki breeding station) and Nevsky; Viza and Gloriya (Falenki breeding station) have good taste. Varieties Virazh (Falenki breeding station), Nevsky, and sample 34-07 are good for chips production because of high content of dry matter and low content of reducing sugars. It has been established that higher humidity during the period of active tuber formation had a negative effect on the content of dry matter and protein in potato tubers (r = -0.88 and -0.89 respectively).